Poppet valve surface anti-corrosion coating process

By chlorinating the carbon nanotubes and grafting them with aminated polytetrafluoroethylene, combined with flexible fluoropolyamide imide, the problem of insufficient compatibility and stability of the modified polytetrafluoroethylene coating is solved, and the coating is improved in high temperature resistance, friction resistance and corrosion resistance.

CN119680859APending Publication Date: 2025-03-25SHANGHAI YONGJIANG ENVIRONMENTAL ENG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510060849.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, the compatibility and stability of the modified polytetrafluoroethylene coating is insufficient, resulting in the coating being easily worn and unable to effectively lift the anti-corrosion performance of the valve surface.

Method used

By acyl chloride treatment of the carbon nanotubes, nitrile-containing carbon nanotubes were obtained and grafted with aminolated polytetrafluoroethylene to form modified polytetrafluoroethylene. At the same time, flexible fluoropolyamide imide is blended with solvent to improve the coating's high temperature resistance, friction resistance and corrosion resistance.

Benefits of technology

It improves the high temperature, friction and corrosion resistance of the coating, enhances the strength and toughness of the coating, extends the service life, and ensures the stability and compatibility of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680859A_ABST
    Figure CN119680859A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-corrosion coating process for the surface of a lift valve, and relates to the technical field of anti-corrosion coatings. The lift valve is characterized by comprising a carbon steel substrate and a titanium plate, the carbon steel base body comprises a bottom plate and a valve ring arranged on the upper surface of the bottom plate, the titanium plate is arranged on the upper surface of the valve ring, and an anti-corrosion coating is arranged on the outer surface of the lifting valve. According to the preparation method disclosed by the invention, the nitrile-group-containing carbon nano tube is obtained by carrying out acylating chlorination treatment on the carbon nano tube and then introducing a nitrile-group functional group, and the nitrile-group functional group is crosslinked in a thermal environment, so that on one hand, the dispersion compatibility of the carbon nano tube and polytetrafluoroethylene is improved, and on the other hand, the interface cohesiveness of the carbon nano tube and the polytetrafluoroethylene is enhanced; the nitrile-group-containing carbon nanotubes are used for modifying polytetrafluoroethylene, so that the high temperature resistance, friction resistance and corrosion resistance of the coating are comprehensively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-corrosion coatings, in particular to a process for anti-corrosion coating on the surface of a lift valve. Background Art

[0002] Teflon, also known as polytetrafluoroethylene, is a fluorocarbon coating with many superior functions, such as high temperature resistance, corrosion resistance, anti-stickiness, friction resistance, high insulation and super hydrophobicity. In order to improve the working performance of metals, Teflon coating is usually applied on their surface.

[0003] CN111378333B discloses a method for preparing a composite modified polytetrafluoroethylene coating, in which inorganic fullerene and carbon fiber are added to a polytetrafluoroethylene emulsion to improve the disadvantage of easy wear of the coating, but the compatibility and stability of the prepared modified polytetrafluoroethylene coating are not mentioned.

[0004] Therefore, we propose a poppet valve surface anti-corrosion coating process to solve the problems raised in the above background technology. Summary of the invention

[0005] The object of the present invention is to provide a process for anti-corrosion coating on the surface of a lift valve to solve the problems raised in the prior art.

[0006] To achieve the above-mentioned object, the present invention provides the following technical solution: a poppet valve, characterized in that it comprises a carbon steel substrate and a titanium plate;

[0007] The carbon steel substrate comprises a bottom plate and a valve ring arranged on the upper surface of the bottom plate, the titanium plate is arranged on the upper surface of the valve ring, and the outer surface of the poppet valve is provided with an anti-corrosion coating.

[0008] Furthermore, the titanium plate and the valve ring are fastened and connected by titanium bolts;

[0009] The bottom plate is fastened to the valve ring by countersunk screws, and the titanium bolts and countersunk screws are made of titanium or titanium alloy.

[0010] The bottom plate and valve ring play a supporting role and serve as a skeleton to ensure the strength of the poppet valve. The use of carbon steel can greatly reduce costs and has certain economic benefits.

[0011] Furthermore, the thickness of the valve ring is 10-12 mm, and the outer diameter and inner diameter of the titanium plate are respectively the same as the outer diameter and inner diameter of the valve ring.

[0012] Furthermore, the titanium plate and the valve ring are provided with matching drilled holes, and the inner wall of the drilled hole of the valve ring is provided with threads that mesh with the titanium bolts;

[0013] The drilled holes of the titanium plate are countersunk through holes that engage with the titanium bolts;

[0014] The diameter of the drilled hole is 0.5 mm larger than the diameter of the titanium bolt. The drilled holes are distributed in a circle array of the titanium plate or valve ring, and the distance between two adjacent sets of drilled hole lines in a horizontal plane is about 100 mm.

[0015] Furthermore, the titanium plate and the valve ring are fastened together by titanium bolts, and then the bolt holes are sealed with welding materials.

[0016] Titanium plate, as a sealing material, can withstand strong acids and alkalis and repeated impact and vibration.

[0017] Furthermore, the plane of the carbon steel substrate and the upper and lower end surfaces of the titanium plate are machined to make the end surfaces flat.

[0018] Furthermore, the valve ring is flatly fitted with the titanium plate, and after being fastened with countersunk screws, the top of the bolt is welded flat with a welding machine to ensure that the valve ring is tightly fitted with the titanium plate, and then the titanium plate is turned again to flatten the end face and chamfer it.

[0019] The provision of titanium bolts enables the valve ring to fit firmly with the titanium plate and withstand certain vibrations. When filling the titanium bolt holes, it can be effectively integrated with the surrounding titanium to avoid the situation where welding is impossible when connected with other materials.

[0020] Furthermore, the entire lift valve is coated with an anti-corrosion coating, except for the sealing surface. After the anti-corrosion coating is applied, it is tested with an electric spark detector to ensure that there are no leaks in the coating.

[0021] The anti-corrosion coating is resistant to high temperatures and strong acids and alkalis, and has good adhesion, and can cover the carbon steel area except the sealing surface.

[0022] Furthermore, the anti-corrosion coating comprises the following components by mass: 10-20 parts of modified polytetrafluoroethylene, 5-15 parts of flexible fluorine-containing polyamide-imide, and 100-120 parts of solvent.

[0023] Furthermore, the modified polytetrafluoroethylene is obtained by reacting amino polytetrafluoroethylene with nitrile-containing carbon nanotubes;

[0024] The flexible fluorine-containing polyamide-imide is obtained by reacting a fluorine-containing diamine with pyromellitic dianhydride.

[0025] The solvent is prepared by mixing dimethylformamide and N-methylpyrrolidone in a volume ratio of 1:1.

[0026] Further, dimethylformamide, CAS No. 68-12-2, was obtained from Jinan Qichen Chemical Co., Ltd.;

[0027] N-Methylpyrrolidone, CAS No. 872-50-4, is from Jinan Chengyijia Chemical Technology Co., Ltd.

[0028] A process for anti-corrosion coating on the surface of a poppet valve comprises the following steps:

[0029] The modified polytetrafluoroethylene, the flexible fluorinated polyamide-imide and the solvent are mixed and stirred evenly at a high speed to obtain a coating, and the coating is sprayed on a poppet valve substrate, dried and cured to obtain an anti-corrosion coating.

[0030] Furthermore, the solvent is a mixed solution of dimethylformamide and N-methylpyrrolidone in a volume ratio of 1:1.

[0031] Furthermore, the mass ratio of modified polytetrafluoroethylene, flexible fluorinated polyamide-imide and solvent is (10-20):(5-15):(100-120).

[0032] Furthermore, the spraying thickness is 18-22 μm.

[0033] Furthermore, the curing process conditions are: temperature 240-280° C., time 0.5-1.5 h.

[0034] Furthermore, the modified polytetrafluoroethylene is prepared by the following process:

[0035] The aminated polytetrafluoroethylene, nitrile-containing carbon nanotubes and dimethylformamide are mixed and heated for reaction. After the reaction is completed, the dimethylformamide is removed and washed to obtain modified polytetrafluoroethylene.

[0036] Furthermore, the ratio of amino polytetrafluoroethylene, nitrile-containing carbon nanotubes and dimethylformamide is (1-10) g: (0.02-0.2) g: (60-600) mL.

[0037] Furthermore, the process conditions of the heating reaction are: temperature 55-75°C, time 45-55h.

[0038] Furthermore, the amino polytetrafluoroethylene is prepared by the following process:

[0039] The polytetrafluoroethylene particles are dried and plasma-modified using ammonia gas to obtain amino-modified polytetrafluoroethylene.

[0040] Further, the process conditions of plasma modification are: voltage 3-5KV, time 40-50s, gas flow rate 5-7L / min;

[0041] The working gas is a mixed gas of ammonia and helium, wherein the volume ratio of ammonia to helium is 1:50.

[0042] Furthermore, polytetrafluoroethylene particles, brand name AP-201, were sourced from Dongguan Zhongming Plastic Co., Ltd.

[0043] Furthermore, the nitrile-containing carbon nanotubes are prepared by the following process:

[0044] S1: placing carbon nanotubes in a mixed acid solution, ultrasonically dispersing for 0.5-1.5 hours, and then heating to react. After the reaction is completed, filtering, washing with water, and drying to obtain carboxylated carbon nanotubes;

[0045] S2: placing the carboxylated carbon nanotubes in S1 in thionyl chloride, adding dimethylformamide, heating and refluxing for reaction, and drying the product after the reaction to obtain acyl chloride carbon nanotubes;

[0046] S3: The acyl chloride carbon nanotubes and 4-aminophthalonitrile in S2 are mixed to obtain a mixed solution, and toluene is added, stirred evenly, reacted at room temperature for 48-72 hours, and centrifuged to obtain a precipitate, which is the nitrile-containing carbon nanotubes.

[0047] Furthermore, the mixed acid solution in S1 is a mixed solution of concentrated sulfuric acid and concentrated nitric acid, wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1;

[0048] The process conditions of the temperature-raising reaction in S1 are: temperature 55-75°C, time 12-24h.

[0049] Further, the ratio of carboxylated carbon nanotubes, thionyl chloride and dimethylformamide in S2 is (0.02-0.2) g: (80-800) mL: (200-2000) mL;

[0050] The process conditions of heating reflux reaction are: temperature 60-80°C, time 12-24h.

[0051] Further, in S3, the mass ratio of acyl chloride carbon nanotubes to 4-aminophthalonitrile is 1:(3-8);

[0052] The mass ratio of the mixed solution to toluene is 1:(5-15).

[0053] Further, carbon nanotubes, CAS No. 1333-86-4, tube diameter 10-15 nm, tube length 10-15 μm, were obtained from Shandong Tanfeng New Materials Technology Co., Ltd.;

[0054] Concentrated sulfuric acid, CAS No. 7664-93-9, from Merck Reagent;

[0055] Concentrated nitric acid, CAS No. 7697-37-2, from Merck Reagent;

[0056] Thionyl chloride, CAS No. 7719-09-7, derived from MacLean's reagent;

[0057] 4-Aminophthalonitrile, CAS No. 56765-79-8, from Wuhan Chengtian Fine Chemical Co., Ltd.;

[0058] Toluene, CAS No. 108-88-3, was obtained from Merck Reagents.

[0059] In the above technical scheme, the carbon nanotubes are subjected to acyl chloride treatment so that the amino group on 4-aminophthalonitrile is grafted with the acyl chloride group to obtain nitrile-containing carbon nanotubes, which are then grafted with amino polytetrafluoroethylene to obtain modified polytetrafluoroethylene. Since the amino group has high activity and the nitrile functional group has strong polarity and can undergo cross-linking in a thermal environment, the grafting reaction between the two improves the dispersion compatibility of the carbon nanotubes and polytetrafluoroethylene on the one hand, and enhances the interfacial adhesion of the carbon nanotubes and polytetrafluoroethylene on the other hand. The carbon nanotubes have good high temperature resistance, are not prone to thermal decomposition or oxidation reaction, and have good wear resistance. Using them to modify polytetrafluoroethylene can comprehensively improve the high temperature resistance, friction resistance and corrosion resistance of the coating. On the other hand, the incompletely reacted acyl chloride group undergoes cross-linking with the amino group in the fluorinated polyamide-imide, which improves the strength and toughness of the coating to a certain extent, makes the coating less likely to break, and prolongs its service life.

[0060] Furthermore, the flexible fluorinated polyamide-imide is prepared by the following process:

[0061] Step 1: Mix a flexible fluorine-containing diamine compound, dimethylformamide and triethylamine, pass a coolant, and stir under a nitrogen atmosphere until the flexible fluorine-containing diamine compound is completely dissolved, then add pyromellitic dianhydride, stir magnetically to react, precipitate, filter, and dry to obtain a fluorine-containing polyamic acid;

[0062] Step 2: Mix the fluorinated polyamic acid in step 1 with dimethylacetamide, add pyridine, acetic anhydride and anhydrous calcium chloride and stir magnetically to react. After the reaction is completed, pour into anhydrous methanol to obtain a filamentous product, and vacuum dry to obtain a flexible fluorinated polyamide imide.

[0063] Furthermore, in step 1, the ratio of the flexible fluorinated diamine compound, dimethylformamide, triethylamine, and pyromellitic dianhydride is (1-3) g: (4-12) mL: (0.5-1.5) mL: (0.7-2.2) g;

[0064] Furthermore, the process conditions of the magnetic stirring reaction are: rotation speed 70-80r / min, time 2-4h.

[0065] Furthermore, the drying process conditions are: temperature 70-90°C, time 8-12h.

[0066] Furthermore, in step 2, the ratio of fluorinated polyamic acid, dimethylacetamide, pyridine, acetic anhydride and anhydrous calcium chloride is (1-6) g: (3-20) mL: (0.3-1.6) g: (0.18-1.2) g: (0.8-5) g.

[0067] Furthermore, the process conditions of the stirring reaction are: rotation speed 70-80r / min, time 1-2h.

[0068] Furthermore, the process conditions of vacuum drying are: temperature 65-85°C, time 6-8h.

[0069] Further, triethylamine, CAS No. 359-70-6, was sourced from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.;

[0070] Pyromellitic dianhydride, CAS No. 89-32-7, from Shandong Jinhe Chemical Co., Ltd.;

[0071] Pyridine, CAS No. 110-86-1, was obtained from Jinan Century Tongda Chemical Co., Ltd.;

[0072] Acetic anhydride, CAS No. 108-24-7, from Merck Reagent;

[0073] Anhydrous calcium chloride, CAS No. 10043-52-4, is derived from MacLean's reagent.

[0074] Furthermore, the flexible fluorine-containing diamine compound is prepared by the following process:

[0075] Pentafluorobenzaldehyde and 4,4'-diaminodiphenyl ether are mixed, heated to 70-80°C under nitrogen atmosphere protection, hydrochloric acid solution is added dropwise at a rate of 2-3 drops / min, the temperature is increased for reaction, and after the reaction is completed, the mixture is cooled to room temperature, extracted 3-5 times, washed 3-5 times, and dried to obtain a flexible fluorine-containing diamine compound.

[0076] Furthermore, the mass fraction of the hydrochloric acid solution is 40%.

[0077] Furthermore, the ratio of pentafluorobenzaldehyde, 4,4'-diaminodiphenyl ether, and hydrochloric acid solution is 1 g: (4-8) g: (0.2-0.6) mL.

[0078] Furthermore, the process conditions of the temperature-raising reaction are: temperature 130-150° C., time 18-24 h.

[0079] Further, pentafluorobenzaldehyde, CAS No. 653-37-2, was sourced from Shanghai Yuanye Biotechnology Co., Ltd.;

[0080] 4,4'-Diaminodiphenyl ether, CAS No. 101-80-4, derived from MacLean's reagent;

[0081] Hydrochloric acid, CAS No. 7647-01-0, was obtained from Merck Reagent.

[0082] In the above technical scheme, pentafluorobenzaldehyde and 4,4'-diaminodiphenyl ether are used as raw materials to synthesize a flexible fluorinated diamine compound, and then a flexible fluorinated polyamide-imide is synthesized through a two-step polycondensation reaction; the flexible fluorinated diamine compound contains ether bonds and fluorine groups, the ether bonds increase the flexibility of the chain, reduce the accumulation of molecular chains, and improve its solubility, the fluorine groups have greater polarity and larger group volume, are more conducive to the diffusion of small solvent molecules, and improve its solubility, the introduction of ether bonds and fluorine groups comprehensively improves the solubility, thermal stability and hydrophobicity of polyamide-imide.

[0083] Compared with the prior art, the present invention has the following beneficial effects:

[0084] 1. The carbon nanotubes are subjected to acyl chloride treatment, so that the amino groups on 4-aminophthalonitrile are grafted with acyl chloride groups to obtain nitrile-containing carbon nanotubes, which are then grafted with amino polytetrafluoroethylene to obtain modified polytetrafluoroethylene. Since the amino groups have high activity and the nitrile functional groups have strong polarity and can undergo cross-linking in a thermal environment, the grafting reaction between the two improves the dispersion compatibility of the carbon nanotubes and polytetrafluoroethylene on the one hand, and enhances the interfacial adhesion of the carbon nanotubes and polytetrafluoroethylene on the other hand. The carbon nanotubes have good high temperature resistance, are not prone to thermal decomposition or oxidation reaction, and have good wear resistance. Using the carbon nanotubes to modify polytetrafluoroethylene can comprehensively improve the high temperature resistance, friction resistance and corrosion resistance of the coating. On the other hand, the incompletely reacted acyl chloride groups undergo cross-linking with the amino groups in the fluorinated polyamide-imide, which improves the strength and toughness of the coating to a certain extent, makes the coating less prone to breakage, and prolongs its service life.

[0085] 2. A flexible fluorinated diamine compound was synthesized using pentafluorobenzaldehyde and 4,4'-diaminodiphenyl ether as raw materials, and then a flexible fluorinated polyamide-imide was synthesized through a two-step polycondensation reaction. The flexible fluorinated diamine compound contains ether bonds and fluorine groups. The ether bonds increase the flexibility of the chain, reduce the accumulation of molecular chains, and improve its solubility. The fluorine groups have greater polarity and larger group volume, which are more conducive to the diffusion of small solvent molecules and improve their solubility. The introduction of ether bonds and fluorine groups comprehensively improves the solubility, thermal stability and hydrophobicity of polyamide-imide. BRIEF DESCRIPTION OF THE DRAWINGS

[0086] Figure 1 It is a schematic diagram of the cross-sectional structure of a lifting valve of the present invention;

[0087] Figure 2 It is a schematic diagram of the cross-sectional structure of a poppet valve of the present invention;

[0088] Figure 3 The figure is a schematic diagram of the overall structure of a lifting valve of the present invention.

[0089] In the figure, 1. base plate, 2. valve ring, 3. titanium plate, 4. titanium bolts; 5. anti-corrosion coating; 6. carbon steel substrate. DETAILED DESCRIPTION

[0090] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0091] In the following specific implementations,

[0092] Polytetrafluoroethylene particles, brand AP-201, from Dongguan Zhongming Plastic Co., Ltd.;

[0093] Dimethylformamide, CAS No. 68-12-2, from Jinan Qichen Chemical Co., Ltd.;

[0094] N-Methylpyrrolidone, CAS No. 872-50-4, from Jinan Chengyijia Chemical Technology Co., Ltd.;

[0095] Carbon nanotubes, CAS No. 1333-86-4, diameter 10-15 nm, length 10-15 μm, from Shandong Tanfeng New Materials Technology Co., Ltd.;

[0096] Concentrated sulfuric acid, CAS No. 7664-93-9, from Merck Reagent;

[0097] Concentrated nitric acid, CAS No. 7697-37-2, from Merck Reagent;

[0098] Thionyl chloride, CAS No. 7719-09-7, derived from MacLean's reagent;

[0099] 4-Aminophthalonitrile, CAS No. 56765-79-8, from Wuhan Chengtian Fine Chemical Co., Ltd.;

[0100] Toluene, CAS No. 108-88-3, from Merck Reagent;

[0101] Triethylamine, CAS No. 359-70-6, was obtained from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.;

[0102] Pyromellitic dianhydride, CAS No. 89-32-7, from Shandong Jinhe Chemical Co., Ltd.;

[0103] Pyridine, CAS No. 110-86-1, was obtained from Jinan Century Tongda Chemical Co., Ltd.;

[0104] Acetic anhydride, CAS No. 108-24-7, from Merck Reagent;

[0105] Anhydrous calcium chloride, CAS No. 10043-52-4, derived from MacLean's reagent;

[0106] Pentafluorobenzaldehyde, CAS No. 653-37-2, was obtained from Shanghai Yuanye Biotechnology Co., Ltd.;

[0107] 4,4'-Diaminodiphenyl ether, CAS No. 101-80-4, derived from MacLean's reagent;

[0108] Hydrochloric acid, CAS No. 7647-01-0, from Merck Reagent;

[0109] Polyamide-imide, model 4200, from Shanghai Beidaer New Materials Co., Ltd.;

[0110] Prepare the solvent: mix dimethylformamide and N-methylpyrrolidone in a volume ratio of 1:1 to obtain a solvent.

[0111] Embodiment 1: A process for applying an anti-corrosion coating on the surface of a poppet valve, comprising the following steps:

[0112] (1) Preparation of modified polytetrafluoroethylene:

[0113] The polytetrafluoroethylene particles are dried and plasma-modified with ammonia to obtain amino polytetrafluoroethylene; the process conditions of the plasma modification are: voltage 3KV, time 40s, gas flow rate 5L / min; the working gas is a mixed gas of ammonia and helium, wherein the volume ratio of ammonia to helium is 1:50;

[0114] S1: Place the carbon nanotubes in a mixed acid solution, perform ultrasonic dispersion for 0.5h, and then heat the solution for reaction. After the reaction, filter, wash, and dry the solution to obtain carboxylated carbon nanotubes. S2: Place the carboxylated carbon nanotubes in S1 in thionyl chloride, add dimethylformamide, heat under reflux for reaction, and after the reaction, dry the product to obtain chlorinated carbon nanotubes. S3: Mix the chlorinated carbon nanotubes in S2 and 4-aminophthalonitrile to obtain a mixed solution, add toluene, stir evenly, react at room temperature for 48h, and centrifuge to obtain a precipitate containing nitrile. The mixed acid solution in S1 is a mixed solution of concentrated sulfuric acid and concentrated nitric acid, wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1; the process conditions of the temperature reaction in S1 are: temperature 55°C, time 12h; the ratio of carboxylated carbon nanotubes, thionyl chloride and dimethylformamide in S2 is 0.02g:80mL:200mL; the process conditions of the heating reflux reaction are: temperature 60-80°C, time 12-24h; the molar ratio of acyl chloride carbon nanotubes and 4-aminophthalonitrile in S3 is 1:3; the mass ratio of the mixed solution to toluene is 1:5;

[0115] The aminated polytetrafluoroethylene, the nitrile-containing carbon nanotubes and dimethylformamide are mixed and heated for reaction. After the reaction is completed, the dimethylformamide is removed and washed to obtain modified polytetrafluoroethylene. The ratio of the aminated polytetrafluoroethylene, the nitrile-containing carbon nanotubes and the dimethylformamide is 1g:0.02g:60mL. The process conditions of the heating reaction are: temperature 55°C, time 45h.

[0116] (2) Preparation of flexible fluorinated polyamide-imide:

[0117] Pentafluorobenzaldehyde and 4,4'-diaminodiphenyl ether are mixed, heated to 70°C under nitrogen atmosphere protection, and hydrochloric acid solution is added at a rate of 2 drops / min for temperature reaction. After the reaction is completed, the mixture is cooled to room temperature, extracted 3 times, washed 3 times, and dried to obtain a flexible fluorine-containing diamine compound; the mass fraction of the hydrochloric acid solution is 40%; the ratio of pentafluorobenzaldehyde, 4,4'-diaminodiphenyl ether, and hydrochloric acid solution is 1g:4g:0.2mL; the process conditions of the temperature reaction are: temperature 130°C, time 18h;

[0118] Step 1: Mix a flexible fluorine-containing diamine compound, dimethylformamide and triethylamine, pass a coolant, and stir under a nitrogen atmosphere until the flexible fluorine-containing diamine compound is completely dissolved, then add pyromellitic acid dianhydride, magnetically stir to react, precipitate, filter, and dry to obtain a fluorine-containing polyamic acid; Step 2: Mix the fluorine-containing polyamic acid in step 1 with dimethylacetamide, add pyridine, acetic anhydride, and anhydrous calcium chloride, magnetically stir to react, pour into anhydrous methanol after the reaction is completed, obtain a filamentous product, and vacuum dry to obtain a flexible fluorine-containing polyamide imide; The flexible fluorine-containing diamine compound in step 1 The ratio of the compound, dimethylformamide, triethylamine, and pyromellitic anhydride is 1g:4mL:0.5mL:0.7g; the process conditions for the magnetic stirring reaction are: speed 70r / min, time 2h; the process conditions for drying are: temperature 70°C, time 8h; the ratio of fluorinated polyamic acid, dimethylacetamide, pyridine, acetic anhydride and anhydrous calcium chloride in step 2 is 1g:3mL:0.3g:0.18g:0.8g; the process conditions for the stirring reaction are: speed 70r / min, time 1h; the process conditions for vacuum drying are: temperature 65°C, time 6h;

[0119] (3) Preparation of anti-corrosion coating:

[0120] Modified polytetrafluoroethylene, flexible fluorinated polyamide-imide and solvent are mixed in a mass ratio of 10:5:100, stirred evenly at high speed to obtain a coating, and the coating is sprayed on a poppet valve substrate, dried, and cured to obtain an anti-corrosion coating; the spraying thickness is 18 μm; the curing process conditions are: temperature 240° C., time 0.5 h.

[0121] Embodiment 2: A process for applying an anti-corrosion coating on the surface of a poppet valve, comprising the following steps:

[0122] (1) Preparation of modified polytetrafluoroethylene:

[0123] The polytetrafluoroethylene particles are dried and plasma-modified with ammonia to obtain amino polytetrafluoroethylene; the process conditions of the plasma modification are: voltage 4KV, time 45s, gas flow rate 6L / min; the working gas is a mixed gas of ammonia and helium, wherein the volume ratio of ammonia to helium is 1:50;

[0124] S1: placing carbon nanotubes in a mixed acid solution, ultrasonically dispersing for 1 hour, and then heating to react. After the reaction, filtering, washing, and drying are performed to obtain carboxylated carbon nanotubes; S2: placing the carboxylated carbon nanotubes in S1 in thionyl chloride, adding dimethylformamide, heating under reflux reaction, and after the reaction is completed, drying the product to obtain acyl chloride carbon nanotubes; S3: mixing the acyl chloride carbon nanotubes in S2 and 4-aminophthalonitrile to obtain a mixed solution, then adding toluene, stirring evenly, reacting at room temperature for 36 hours, and centrifuging to obtain a precipitate containing Nitrile carbon nanotubes; the mixed acid solution in S1 is a mixed solution of concentrated sulfuric acid and concentrated nitric acid, wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1; the process conditions of the temperature-raising reaction in S1 are: temperature 65°C, time 18h; the ratio of carboxylated carbon nanotubes, thionyl chloride and dimethylformamide in S2 is 0.1g:500mL:1000mL; the process conditions of the heating reflux reaction are: temperature 70°C, time 18h; the molar ratio of acyl chloride carbon nanotubes and 4-aminophthalonitrile in S3 is 1:5; the mass ratio of the mixed solution to toluene is 1:10;

[0125] The aminated polytetrafluoroethylene, the nitrile-containing carbon nanotubes and dimethylformamide are mixed and heated for reaction. After the reaction is completed, the dimethylformamide is removed and washed to obtain modified polytetrafluoroethylene. The ratio of the aminated polytetrafluoroethylene, the nitrile-containing carbon nanotubes and the dimethylformamide is 5g:0.1g:300mL. The process conditions of the heating reaction are: temperature 65°C, time 50h.

[0126] (2) Preparation of flexible fluorinated polyamide-imide:

[0127] Pentafluorobenzaldehyde and 4,4'-diaminodiphenyl ether are mixed, heated to 75°C under nitrogen atmosphere protection, and hydrochloric acid solution is added at a rate of 2 drops / min for temperature reaction. After the reaction is completed, the mixture is cooled to room temperature, extracted 4 times, washed 4 times, and dried to obtain a flexible fluorine-containing diamine compound; the mass fraction of the hydrochloric acid solution is 40%; the ratio of pentafluorobenzaldehyde, 4,4'-diaminodiphenyl ether, and hydrochloric acid solution is 1g:6g:0.4mL; the process conditions of the temperature reaction are: temperature 140°C, time 20h;

[0128] Step 1: Mix a flexible fluorine-containing diamine compound, dimethylformamide and triethylamine, pass a coolant, and stir under a nitrogen atmosphere until the flexible fluorine-containing diamine compound is completely dissolved, then add pyromellitic acid dianhydride, magnetically stir to react, precipitate, filter, and dry to obtain a fluorine-containing polyamic acid; Step 2: Mix the fluorine-containing polyamic acid in step 1 with dimethylacetamide, add pyridine, acetic anhydride, and anhydrous calcium chloride, magnetically stir to react, pour into anhydrous methanol after the reaction is completed, obtain a filamentous product, and vacuum dry to obtain a flexible fluorine-containing polyamide imide; The flexible fluorine-containing diamine compound in step 1 The ratio of the compound, dimethylformamide, triethylamine, and pyromellitic acid anhydride is 2g:8mL:1mL:1.5g; the process conditions for the magnetic stirring reaction are: speed 75r / min, time 3h; the process conditions for drying are: temperature 80℃, time 10h; the ratio of fluorinated polyamic acid, dimethylacetamide, pyridine, acetic anhydride and anhydrous calcium chloride in step 2 is 3g:12mL:1g:0.6g:2.5g; the process conditions for the stirring reaction are: speed 75r / min, time 1.5h; the process conditions for vacuum drying are: temperature 75℃, time 7h;

[0129] (3) Preparation of anti-corrosion coating:

[0130] Modified polytetrafluoroethylene, flexible fluorinated polyamide-imide and solvent are mixed in a mass ratio of 15:10:110, stirred evenly at high speed to obtain a coating, sprayed on a poppet valve substrate, dried, and cured to obtain an anti-corrosion coating; the spraying thickness is 20 μm; the curing process conditions are: temperature 260° C., time 1 hour.

[0131] Embodiment 3: A process for applying an anti-corrosion coating on the surface of a poppet valve, comprising the following steps:

[0132] (1) Preparation of modified polytetrafluoroethylene:

[0133] The polytetrafluoroethylene particles are dried and plasma-modified with ammonia to obtain amino polytetrafluoroethylene; the process conditions of the plasma modification are: voltage 5KV, time 50s, gas flow rate 7L / min; the working gas is a mixed gas of ammonia and helium, wherein the volume ratio of ammonia to helium is 1:50;

[0134] S1: placing carbon nanotubes in a mixed acid solution, ultrasonically dispersing for 1.5 hours, and then heating to react. After the reaction, filter, wash with water, and dry to obtain carboxylated carbon nanotubes; S2: placing the carboxylated carbon nanotubes in S1 in thionyl chloride, adding dimethylformamide, heating under reflux reaction, and after the reaction, drying the product to obtain acyl chloride carbon nanotubes; S3: mixing the acyl chloride carbon nanotubes in S2 and 4-aminophthalonitrile to obtain a mixed solution, then adding toluene, stirring evenly, reacting at room temperature for 72 hours, and centrifuging to obtain the precipitate obtained. Containing nitrile-based carbon nanotubes; the mixed acid solution in S1 is a mixed solution of concentrated sulfuric acid and concentrated nitric acid, wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1; the process conditions of the temperature-raising reaction in S1 are: temperature 75°C, time 24h; the ratio of carboxylated carbon nanotubes, thionyl chloride and dimethylformamide in S2 is 0.2g:800mL:2000mL; the process conditions of the heating reflux reaction are: temperature 80°C, time 24h; the molar ratio of acyl chloride carbon nanotubes and 4-aminophthalonitrile in S3 is 1:3; the mass ratio of the mixed solution to toluene is 1:15;

[0135] The aminated polytetrafluoroethylene, the nitrile-containing carbon nanotubes and dimethylformamide are mixed and heated for reaction. After the reaction is completed, the dimethylformamide is removed and washed to obtain modified polytetrafluoroethylene. The ratio of the aminated polytetrafluoroethylene, the nitrile-containing carbon nanotubes and the dimethylformamide is 10g:0.2g:600mL. The process conditions of the heating reaction are: temperature 75°C, time 55h.

[0136] (2) Preparation of flexible fluorinated polyamide-imide:

[0137] Pentafluorobenzaldehyde and 4,4'-diaminodiphenyl ether are mixed, heated to 80°C under nitrogen atmosphere protection, and hydrochloric acid solution is added at a rate of 3 drops / min for temperature reaction. After the reaction is completed, the mixture is cooled to room temperature, extracted 5 times, washed 5 times, and dried to obtain a flexible fluorine-containing diamine compound; the mass fraction of the hydrochloric acid solution is 40%; the ratio of pentafluorobenzaldehyde, 4,4'-diaminodiphenyl ether, and hydrochloric acid solution is 1g:8g:0.6mL; the process conditions of the temperature reaction are: temperature 150°C, time 24h;

[0138] Step 1: Mix a flexible fluorine-containing diamine compound, dimethylformamide and triethylamine, pass a coolant, and stir under a nitrogen atmosphere until the flexible fluorine-containing diamine compound is completely dissolved, then add pyromellitic acid dianhydride, magnetically stir to react, precipitate, filter, and dry to obtain a fluorine-containing polyamic acid; Step 2: Mix the fluorine-containing polyamic acid in step 1 with dimethylacetamide, add pyridine, acetic anhydride, and anhydrous calcium chloride, magnetically stir to react, pour into anhydrous methanol after the reaction is completed, obtain a filamentous product, and vacuum dry to obtain a flexible fluorine-containing polyamide imide; The flexible fluorine-containing diamine compound in step 1 The ratio of the compound, dimethylformamide, triethylamine, and pyromellitic acid anhydride is 3g:12mL:1.5mL:2.2g; the process conditions for the magnetic stirring reaction are: speed 80r / min, time 4h; the process conditions for drying are: temperature 90°C, time 12h; the ratio of fluorinated polyamic acid, dimethylacetamide, pyridine, acetic anhydride and anhydrous calcium chloride in step 2 is 6g:20mL:1.6g:1.2g:5g; the process conditions for the stirring reaction are: speed 80r / min, time 2h; the process conditions for vacuum drying are: temperature 85°C, time 8h;

[0139] (3) Preparation of anti-corrosion coating:

[0140] Modified polytetrafluoroethylene, flexible fluorinated polyamide-imide and solvent are mixed in a mass ratio of 20:15:120, stirred evenly at high speed to obtain a coating, sprayed on a poppet valve substrate, dried, and cured to obtain an anti-corrosion coating; the spraying thickness is 22 μm; the curing process conditions are: temperature 280° C., time 1.5 h.

[0141] Comparative Example 1: Taking Example 1 as an example, the nitrile-containing carbon nanotubes were replaced with commercially available carbon nanotubes, and the other conditions remained unchanged.

[0142] Comparative Example 2: Taking Example 1 as an example, the flexible fluorinated polyamide-imide is replaced with commercially available polyamide-imide, and the other conditions remain unchanged.

[0143] Comparative Example 3: Taking Example 1 as an example, no nitrile-containing carbon nanotubes were added, and other conditions remained unchanged.

[0144] Comparative Example 4: Taking Example 1 as an example, no nitrile-containing carbon nanotubes are added, and the flexible fluorine-containing polyamide-imide is replaced with commercially available polyamide-imide, and other conditions remain unchanged.

[0145] Experiment: The anticorrosion coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were tested for various properties;

[0146] Corrosion resistance test: Q-FOG SSP-1100 cyclic salt spray corrosion test chamber is used to test the corrosion resistance of the anti-corrosion coating;

[0147] Wear resistance test: The coating was tested for wear using a TABER 5135 testing machine;

[0148] High temperature resistance test: The titanium substrate coated with the coating was placed in a 350°C environment for 100 hours, and its appearance changes were recorded. The test results are as follows:

[0149] The following table shows the test results of the coating's corrosion resistance, wear resistance and high temperature resistance.

[0150] Corrosion resistance Wear amount / mg High temperature resistance Example 1 No significant changes 4.1 No significant changes Example 2 No significant changes 3.5 No significant changes Example 3 No significant changes 2.6 No significant changes Comparative Example 1 Slightly foamy 5.5 No significant changes Comparative Example 2 Slightly foamy 4.9 Slight bubbling, slight cracking Comparative Example 3 Slight bubbling, slight cracking 6.4 Slight bubbling, slight cracking Comparative Example 4 More bubbles, cracking, severe 8.4 More bubbles and severe cracking

[0151] From the test results in the above table, we can clearly draw the following conclusions:

[0152] The coatings obtained in Examples 1 to 3 are compared with the coatings obtained in Comparative Examples 1 to 4. The test results show that:

[0153] Compared with Example 1, in Comparative Example 1, the nitrile-containing carbon nanotubes are replaced with commercially available carbon nanotubes, and the corrosion resistance and wear resistance of the carbon nanotubes are reduced. The reason is that the dispersibility of the carbon nanotubes that have not been surface-modified in the coating is reduced, which may cause the coating to be uneven and not dense, so the corrosion resistance and wear resistance are reduced.

[0154] In Comparative Example 2, the flexible fluorinated polyamide-imide is replaced with commercially available polyamide-imide, and its high temperature resistance and corrosion resistance are reduced. The reason is that the commercially available polyamide-imide has poor solubility, which may cause uneven coating, so the high temperature resistance and corrosion resistance are reduced.

[0155] In Comparative Example 3, no nitrile-containing carbon nanotubes were added, and various properties were reduced. The reason is that carbon nanotubes have good high temperature resistance and corrosion resistance, and nitrile functional groups have strong polarity and can be cross-linked in a hot environment, which enhances the interfacial adhesion between carbon nanotubes and polytetrafluoroethylene. After removing them, various properties of the coating were reduced.

[0156] In Comparative Example 4, no nitrile-containing carbon nanotubes are added, and the flexible fluorinated polyamide-imide is replaced with commercially available polyamide-imide. Various performances are significantly reduced. It can be seen that the preparation process of the anti-corrosion coating and the setting of the components used in the present application can promote the comprehensive improvement of its high temperature resistance, corrosion resistance and wear resistance.

[0157] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A poppet valve, characterized in that: It comprises a carbon steel substrate (6) and a titanium plate (3); The carbon steel substrate (6) comprises a base plate (1) and a valve ring (2) arranged on the upper surface of the base plate (1), the titanium plate (3) is arranged on the upper surface of the valve ring (2), and the outer surface of the poppet valve is provided with an anti-corrosion coating (5).

2. A poppet valve according to claim 1, characterized in that: The titanium plate (3) and the valve ring (2) are fastened together by titanium bolts (4); The base plate (1) and the valve ring (2) are fastened together by countersunk screws, and the titanium bolts (4) and the countersunk screws are made of titanium or titanium alloy.

3. A poppet valve according to claim 1, characterized in that: The thickness of the valve ring (2) is 10-12 mm, and the outer diameter and inner diameter of the titanium plate (3) are respectively the same as the outer diameter and inner diameter of the valve ring (2).

4. A process for anti-corrosion coating on the surface of a poppet valve according to any one of claims 1 to 3, characterized in that: The anti-corrosion coating is prepared by the following process: The modified polytetrafluoroethylene, the flexible fluorinated polyamide-imide and the solvent are mixed and stirred evenly at a high speed to obtain a coating, and the coating is sprayed on a poppet valve substrate, dried and cured to obtain an anti-corrosion coating.

5. The process for applying an anti-corrosion coating on the surface of a poppet valve according to claim 4, characterized in that: The modified polytetrafluoroethylene is prepared by the following process: The aminated polytetrafluoroethylene, nitrile-containing carbon nanotubes and dimethylformamide are mixed and heated for reaction. After the reaction is completed, the dimethylformamide is removed and washed to obtain modified polytetrafluoroethylene.

6. The process for applying an anti-corrosion coating on the surface of a poppet valve according to claim 4, characterized in that: The flexible fluorinated polyamide-imide is prepared by the following process: Step 1: Mix a flexible fluorine-containing diamine compound, dimethylformamide and triethylamine, pass a coolant, and stir under a nitrogen atmosphere until the flexible fluorine-containing diamine compound is completely dissolved, then add pyromellitic dianhydride, stir magnetically to react, precipitate, filter, and dry to obtain a fluorine-containing polyamic acid; Step 2: Mix the fluorinated polyamic acid in step 1 with dimethylacetamide, add pyridine, acetic anhydride and anhydrous calcium chloride and stir magnetically to react. After the reaction is completed, pour into anhydrous methanol to obtain a filamentous product, and vacuum dry to obtain a flexible fluorinated polyamide imide.

7. The process for applying an anti-corrosion coating on the surface of a poppet valve according to claim 5, characterized in that: The nitrile-containing carbon nanotubes are prepared by the following process: S1: placing carbon nanotubes in a mixed acid solution, ultrasonically dispersing for 0.5-1.5 hours, and then heating to react. After the reaction is completed, filtering, washing with water, and drying to obtain carboxylated carbon nanotubes; S2: placing the carboxylated carbon nanotubes in S1 in thionyl chloride, adding dimethylformamide, heating and refluxing for reaction, and drying the product after the reaction to obtain acyl chloride carbon nanotubes; S3: The acyl chloride carbon nanotubes and 4-aminophthalonitrile in S2 are mixed to obtain a mixed solution, and toluene is added, stirred evenly, reacted at room temperature for 48-72 hours, and centrifuged to obtain a precipitate, which is the nitrile-containing carbon nanotubes.

8. The process for applying an anti-corrosion coating on the surface of a poppet valve according to claim 6, characterized in that: The flexible fluorine-containing diamine compound is prepared by the following process: Pentafluorobenzaldehyde and 4,4'-diaminodiphenyl ether are mixed, heated to 70-80°C under nitrogen atmosphere protection, hydrochloric acid solution is added dropwise at a rate of 2-3 drops / min, the temperature is increased for reaction, and after the reaction is completed, the mixture is cooled to room temperature, extracted 3-5 times, washed 3-5 times, and dried to obtain a flexible fluorine-containing diamine compound.

9. The process for applying an anti-corrosion coating on the surface of a poppet valve according to claim 4, characterized in that: The curing process conditions are: temperature 240-280°C, time 0.5-1.5h.

10. The process for anti-corrosion coating on the surface of a poppet valve according to claim 4, characterized in that: The mass ratio of modified polytetrafluoroethylene, flexible fluorinated polyamide-imide and solvent is (10-20):(5-15):(100-120).

Citation Information

Patent Citations

  • A method for preparing a composite modified polytetrafluoroethylene coating

    CN111378333B